HUBUNGAN KEBIASAAN BERMAIN GAME ONLINE DENGAN PRESTASI BELAJAR PESERTA DIDIK KELAS TINGGI MIN 16 JAKARTA TIMUR - Amanda Salsabilla; Rahmiati Rahmiati; Nurafni Nurafni (STKIP Subang, 2022)
This study aims to determine the relationship between the habit of playing online games with the learning achievement of high grade students at MIN 16 Cipayung, East Jakarta. This research uses Associative Quantitative Research and uses correlation research methods. The tool used to collect data in this study was a questionnaire in the form of a statement in the form of a Likert scale for the habit of playing online games, and report cards for student achievement in the even semester of the 2021/2022 school year. In testing the hypothesis, the product moment correlation test was used to obtain a sig value. (2tailed) 0.03 or < from 0.024, and the correlation value is 0.361. The conclusion of this study shows that there is a relationship between playing online games with the learning achievement of high grade students at MIN 16 East Jakarta.